THE UTILIZATION OF QRIS IN THE ES TELER 88 BUSINESS IN RAPPOCINI DISTRICT, MAKASSAR CITY - ENZEL D. S. SITUMORANG; AGUS SYAM, ASMAYANTI, MUHAMMAD JUFRI, SUMIATI TAHIR (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to examine the use of QRIS (Quick Response Code Indonesian Standard) as a digital payment method at Es Teler 88, a business located in Rappocini District, Makassar City. The focus of the study includes the ease of payment for customers, benefits for business owners (merchants), and the positive and negative impacts of QRIS implementation on business operations. This study employs a qualitative descriptive approach with data collection techniques including in-depth interviews, direct observation, and documentation. The results of the study indicate that the use of QRIS provides convenience, speed, and a sense of security in transactions for customers. For business operators, QRIS enhances the modern image of the business, reduces the risk of counterfeit money, facilitates automatic financial record-keeping, and improves efficiency in transaction management. However, some challenges such as technical issues and administrative fees remain as challenges that need to be addressed